2015
DOI: 10.1021/la504495c
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Theory for Capillary-Pressure Hysteresis

Abstract: In this article, we present a theory of macroscopic contact angle hysteresis by considering the minimization of the Helmholtz free energy of a solid-liquid-gas system over a convex set, subject to a constant volume constraint. The liquid and solid surfaces in contact are assumed to adhere weakly to each other, causing the interfacial energy to be set-valued. A simple calculus of variations argument for the minimization of the Helmholtz energy leads to the Young-Laplace equation for the drop surface in contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(82 reference statements)
0
6
1
Order By: Relevance
“…We assume that γ SL take the values in the set [γ SLmin , γ SLmax ]. Justification for this assumption is provided in detail in [4,9].…”
Section: Model Formulation For the Capillary Surfacementioning
confidence: 99%
See 3 more Smart Citations
“…We assume that γ SL take the values in the set [γ SLmin , γ SLmax ]. Justification for this assumption is provided in detail in [4,9].…”
Section: Model Formulation For the Capillary Surfacementioning
confidence: 99%
“…Each cycle of wetting and drying involves a motion of the contact line and subsequent change in the curvature of the capillary interface. These two phenomena correspond to two different mechanisms for energy converted to heat -(i) hysteresis that has its origins in the adhesion between liquid and solid and is quasi-static or rate-independent [4]; (ii) viscous friction that opposes the motion of neighboring fluid molecules. In earlier work [4], we studied the quasi-static hysteresis phenomenon due to capillary effect and showed that the energy required to overcome adhesion while completing a cycle is simply obtained from the area of the graph of capillary pressure versus volume of the liquid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various models of complex hysteresis relationships have been proposed and used by physicists and engineers. A few most prominent models include the Preisach model of magnetic materials, the Prandtl-Ishlinskii model of plasticity and friction and the Ising spin-interaction model of phase transitions in statistical physics (that have been also adapted to model sorption hysteresis [21][22][23][24]; damage accumulation [25]; constitutive laws of "smart" materials; hysteresis in economics [26][27][28], social dynamics and population biology [29][30][31][32]; see [33,34] for further examples). Mathematical tools that have been developed in the area of modeling hysteresis phenomena and systems with hysteretic components are diverse and include the method of hysteresis operators [35], differential inclusions [36], variational inequalities [37], variational approach based on Γ-convergence [38] and switched systems [39].…”
Section: (Left)mentioning
confidence: 99%